Increased Expression of INHBA Is Correlated With Poor Prognosis and High Immune Infiltrating Level in Breast Cancer - Yu, Zeying; Cheng, Li; Liu, Xinlian; Zhang, Lushun; Cao, Hui (Frontiers in Bioinformatics, 2022)
Background: Inhibin, beta A (INHBA) is a member of the transforming growth factor (TGF-β) superfamily and associated with carcinogenesis and cancer progression in several types of human cancers. However, its significance in breast cancer has not been evaluated. Here, we investigated the prognostic value of INHBA and its correlation with tumor-infiltration immune cells in the microenvironment of breast cancer. Methods: In this study, we analyzed the INHBA expression profile in the Oncomine database and Tumor Immune Estimation Resource 2.0 (TIMER2.0) site. Using Breast Cancer Gene-Expression Miner (bc-GenExMiner v4.7) tool and UALCAN cancer database, we further evaluated the correlation of INHBA expression with clinicopathological factors in breast cancer. Then, we assessed clinical prognostic value of INHBA using Kaplan-Meier Plotter and the PrognoScan databases. The correlations between INHBA and tumor-infiltrating immune cells were investigated via TIMER2.0. In addition, correlations between INHBA expression and gene markers of immune inﬁltrates were analyzed by TIMER2.0 and Gene Expression Profiling Interactive Analysis (GEPIA2). Results: Compared with the level in normal tissues, the INHBA mRNA expression was upregulated in different subtypes of breast cancer, and its expression was positively correlated with progesterone receptor (PR), human epidermal growth factor receptor-2 (HER-2) status and PAM50 subtypes, but negatively related to age and basal-like status. The INHBA protein was also highly expressed in primary breast cancer and closely related to pathological stage. Patients with high INHBA expression level showed worse overall survival (OS), relapse-free survival (RFS) and distant metastasis-free survival (DMFS). And high INHBA expression was significantly associated with worse OS and RFS in positive lymph nodes. Of interest, INHBA expression was negatively correlated with inﬁltrating levels of activated NK cells, NKT and CD4+ T cells, but was positively correlated with tumor inﬁltration of CD8+ T cells, neutrophils, especially macrophages and cancer-associated fibroblasts (CAFs). Moreover, INHBA expression showed strong correlations with various markers of monocytes/macrophages and CAFs. Conclusions: High INHBA expression is correlated with poor prognosis and the infiltration of immune cells in the tumor microenvironment. These findings suggest that INHBA may be involved in immune escape and can serve as a potential biomarker of prognosis and tumor-infiltrating immune cells